Government Ideology, Globalization, and Top Income Shares in OECD Countries - Christoph Schinke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
I investigate how government ideology and globalization are associated with top income shares in 16 OECD countries over the period 1970 to 2010. I use the new World Top Incomes Database. Globalization is measured by the KOF index of globalization. The results show that the top 1% income share increased more under rightwing governments than under leftwing governments. The effect was stronger when globalization proceeded more rapidly.
Keywords: D31; D72; F62; H80; N30; 330; Inequality; partisan theory; globalization; panel data models